PENDIDIKAN POLITIK BAGI MASYARAKAT MENJELANG PEMILU TAHUN 2024 DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 7 TAHUN 2017 - Harmoko, Harmoko; Oktaviani, Dewi Anggun; Maksin, Mastina; Astuti N, Veronica Sri; Wahyono, Eko; Su'ud, Moch.; Herlambang, Tedy; Wati, Rahma; Kusniawati, Noer Aini (Abdi Panca Marga, 2023)
Political education is a process and learning about the rights, duties and responsibilities of every citizen in the life of the nation and state. The implementation of the civil service program raises the problem of a lack of understanding of political education ahead of the election from the point of view of Law no. 7 of 2017 for residents of the Traditional Village of Dringu District. To overcome these problems, political education advice is given with the aim of increasing knowledge, understanding, understanding and awareness as well as interest in voicing the right to vote in elections. The method used is to speak directly to the community. Political education in elections in the democratic state of Indonesia is considered to be still not high. Due to mixed feelings, many people voted for white citizens (abstained) in the elections. One effort to overcome this problem is to organize political education for the indigenous people themselves. Indigenous peoples are expected to become a generation of political education and political conditions, punishment for disturbance and understanding of political education in one of its parts. Promoting political education also strives for local cultural communities not only to become political objects but also to act as political subjects. Keywords: Educatian, politics, and elections.